2020
DOI: 10.1172/jci.insight.137528
|View full text |Cite
|
Sign up to set email alerts
|

TRPV4 blockade suppresses atrial fibrillation in sterile pericarditis rats

Abstract: Atrial fibrillation (AF) commonly occurs after surgery and is associated with atrial remodeling. TRPV4 is functionally expressed in the heart, and its activation affects cardiac structure and functions. We hypothesized that TRPV4 blockade alleviates atrial remodeling and reduces AF induction in sterile pericarditis (SP) rats. TRPV4 antagonist GSK2193874 or vehicle was orally administered 1 d before pericardiotomy. AF susceptibility and atrial function were assessed using in vivo electrophysiology, ex vivo opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 41 publications
8
29
0
Order By: Relevance
“…Previous studies demonstrated that the JAK2–STAT3 pathway is involved in glial activation and cytokine expression [ 58 60 ]. Moreover, in the context of neurological inflammatory signaling cascades, TRPV4 reportedly exacerbates neuro-inflammatory actions through the activation of pro-inflammatory STAT3 signaling [ 61 , 62 ]. Furthermore, the inhibition of STAT3 phosphorylation via JAK2 blockade has been shown to reduce hypoxic ischemia-induced neuroinflammation and tissue loss [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that the JAK2–STAT3 pathway is involved in glial activation and cytokine expression [ 58 60 ]. Moreover, in the context of neurological inflammatory signaling cascades, TRPV4 reportedly exacerbates neuro-inflammatory actions through the activation of pro-inflammatory STAT3 signaling [ 61 , 62 ]. Furthermore, the inhibition of STAT3 phosphorylation via JAK2 blockade has been shown to reduce hypoxic ischemia-induced neuroinflammation and tissue loss [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative atrial fibrillation (POAF), the most common complication of cardiac surgery, the prevalence of which varies between 20% and 40% in different studies, usually occurs 2-4 days after surgery, causing substantial increases in lengths and costs of hospital stay ( 1 ). Local inflammation, which is related to surgical lesions and postoperative pericarditis, is a major transient factor that may trigger POAF ( 2 6 ). Some clinical observations suggest that interleukin (IL)-6, a crucial pro-inflammatory cytokine, is elevated in patients with POAF ( 7 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some clinical observations suggest that interleukin (IL)-6, a crucial pro-inflammatory cytokine, is elevated in patients with POAF ( 7 9 ). Moreover, IL-6 is early upregulated in the atria of rat and canine sterile pericarditis (SP), which are animal models of POAF ( 2 5 ). We found that IL-6 predisposes to atrial fibrosis and fibrillation by inducing cardiac fibroblast activation in SP rats ( 3 , 4 ), which is further confirmed by Liu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the mechanistic link between TRPCs and Ca 2+ mishandling has been reported in multiple experimental models of cardiac disease including myocardial infarction [ 66 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ], atrial fibrillation [ 88 , 89 , 90 , 91 ], and iron overload cardiomyopathy [ 92 ]. In addition to TRPCs, other members of the TRP superfamily [ 93 , 94 , 95 ], e.g., melastatin (TRPM) [ 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 ] and vanilloid (TRPV) subtypes [ 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 ], are also potential candidates mediating the non-canonical Ca 2+ entry into cardiomyocytes.…”
Section: Calcium Cycling In Pressure Overload Hypertrophy Dysthyroidism and Human Heart Failurementioning
confidence: 99%